Question: If cos A = \dfrac{1}{2} \left ( a +\dfrac{1}{a} \right), show that:


cos 2A = \dfrac{1}{2} \left ( a² + \dfrac{1}{a²} \right)


Solution:
Given,
cos A = \dfrac{1}{2} \left ( a +\dfrac{1}{a} \right)


We know,
cos 2A
= 2cos²A - 1

= 2 (cosA)² -1

= 2 \left \{  \dfrac{1}{2} \left ( a + \dfrac{1}{a} \right) \right \}^2 -1

= 2 \left \{ \dfrac{1}{4} \left ( a² + 2 + \dfrac{1}{a²} \right) \right \} -1

= \dfrac{ \left ( a² + 2 + \dfrac{1}{a²} \right) }{2}  -1

= \dfrac{ a² +2 +\dfrac{1}{a²} -2 }{2}

= \dfrac{a² +\dfrac{1}{a²}

= \dfrac{1}{2} \left ( a² + \dfrac{1}{a²} \right )
= RHS

Related Notes And Solutions:

Link: Introduction To Trigonometry
Link: Values of Trigonometric Ratios
Link: Compound Angles

#SciPiPupil